A global history of trade and conflict since 1500 - Coppolaro, Lucia; McKenzie, Francine, 1967- (New York : Palgrave Macmillan, 2013)
'This volume is a major historical contribution to the enduring debate about whether trade makes peace more likely. In nine detailed historical case studies - spread over 500 years and spanning the globe - the contributors explore the dynamic between trade and conflict and examine the consequences of their intersection, direct and indirect, immediate and long term, anticipated and unexpected, transformative and destructive. The contributors break new ground by collectively showing that trade and conflict have been reciprocally constitutive: trade sparks conflict and conflict in turn provokes the adaptation of trade. Scholars who affirm a close association between trade and peace will have to take into account the close and persistent connection between trade and conflict, as will the makers of current trade policy'--
Machine generated contents note: -- Acknowledgements -- List of Figures -- List of Abbreviations -- Notes on Contributors -- Introduction: The Intersection of Trade and Conflict Since 1500; Francine McKenzie -- 1. Trade and Conflict in the South China Sea: Portugal and China, 1514-1523; Timothy Brook -- 2. Portuguese Resilience in Global Trade: Military Motivation and Institutional Adaptation in the 16th and 17th Century Cape Route; Leonor Freire Costa -- 3. An Explosion of Violence: How the Haitian Revolution Rearranged the Trade Patterns of the Western Hemisphere; Steven Topik -- 4. Lifting the Continental Blockade: Britain, Portugal and Brazilian Trade in the Global Context of the Napoleonic Wars; Jose; Lui;s Cardoso -- 5. Retreating from Globalisation: Britain and the Renewal of Imperial Trade Between the Two World Wars; Tim Rooth -- 6. Trade and Conflict in the Rhetoric of Winston Churchill; Richard Toye -- 7. War, Revolution and the Great Depression in the Global Wheat Trade, 1917-1939; Gregory P. Marchildon -- 8. Trading Blocs and Trading Blows: GATT's Conflictual Path to Trade Liberalisation, 1947-1967; Lucia Coppolaro and Francine McKenzie -- 9. Nixon's War with the International Economy; Thomas W. Zeiler -- Conclusion: Dismissing the Kantian View of Trade and Peace; Renato G. Flores Jr. -- Bibliography.
Includes bibliographical references (pages 220-238) and index.
Keywords: International trade -- History; Conflict of interests; International economic relations -- History